2021
DOI: 10.3390/ijerph18010337
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Traumatic Stress and Burnout in Healthcare Workers during COVID-19 Outbreak

Abstract: (1) Background: The present study aims to assess the level of professional burnout and secondary traumatic stress (STS), and to identify potential risk or protective factors among health care workers (HCWs) during the coronavirus disease 2019 (COVID-19) outbreak.; (2) Methods: This cross-sectional study, based on an online survey, collected demographic data and mental distress outcomes from 184 HCWs from 1 May 2020, to 15 June 2020, from 45 different countries. The degree of STS, perceived stress and burnout w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
141
3
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 176 publications
(205 citation statements)
references
References 37 publications
(32 reference statements)
19
141
3
4
Order By: Relevance
“…This was consistent with a multinational study carried out in 45 countries to explore the prevalence of BOS among health-care professionals during the first wave of the COVID-19 pandemic. It was found that about half (56%) of the cohort showed high EE, 48.9% recorded high depersonalization, and about one-third (38%) showed low PA [34].…”
Section: Discussionmentioning
confidence: 95%
“…This was consistent with a multinational study carried out in 45 countries to explore the prevalence of BOS among health-care professionals during the first wave of the COVID-19 pandemic. It was found that about half (56%) of the cohort showed high EE, 48.9% recorded high depersonalization, and about one-third (38%) showed low PA [34].…”
Section: Discussionmentioning
confidence: 95%
“…Frontline workers reported higher level of perceived stress, emotional exhaustion and depersonalization than their colleagues working in other units. It may be, as some have argued, that direct work with COVID-19 patients constitutes a cumulative vicarious trauma for frontline workers with direct effects on stress and burnout [ 60 , 61 ]. Notably, no differences were found in personal accomplishment and resilience among these two groups of healthcare workers, perhaps suggesting that the structural components of strengths-based, psychological functioning are not influenced by time-limited stressful experiences.…”
Section: Discussionmentioning
confidence: 99%
“…The tool comprises 30 items, with 10 items each on compassion satisfaction, secondary traumatic stress, and burnout, and each item is rated on a five-point Likert scale ranging from "strongly disagree" (1) to "strongly agree" (5). The total score range is 10-50; scores are classified as low (≤22), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), and high (≥42), and higher scores indicate higher compassion satisfaction, secondary traumatic stress, and burnout. As suggested by the developer, the total score was standardized to a t-score with a mean of 50 ± 10.…”
Section: Professional Quality Of Lifementioning
confidence: 99%